Are Competence Beliefs or Value Beliefs More Important for STEM Career Aspirations?—Longitudinal Mediation Analyses Based on Recent Modeling Approaches Show Different Results - Debatin, Tobias; Stoeger, Heidrun; Ziegler, Albert (Journal of Youth and Adolescence, 2025)
There is a consensus in situated expectancy-value theory research that value beliefs better predict career aspirations and choices than competence beliefs and thus should be the main target of interventions aimed to motivate youth for STEM (science, technology, engineering, math) careers. However, research on the longer-term causal effects of the two constructs and their indirect effects is missing. The latter is relevant since competence beliefs seem to influence value beliefs but less the other way around. The present study investigated such longer-term effects and the underlying indirect effects in a sample of 690 students from Germany (52.6% girls; M (T1) = 15.26 years, SD = 0.68) over three measurement points from the middle of Grade 9 to the middle of Grade 10. For these purposes, two recent models with improved properties for identifying causal effects, the random intercept cross-lagged panel model (RI-CLPM) and the dynamic panel model, as well as the traditional CLPM were applied. Final analyses were based on the RI-CLPM, and the results were compared to the traditional CLPM. Both models found the expected tendency of higher effects of STEM value beliefs on STEM career aspirations from one time point to the next. However, regarding the longer-term total effects, the analysis based on the RI-CLPM found a slight tendency for larger effects of competence beliefs, including an indirect effect of competence beliefs via value beliefs. These findings indicate that the competence beliefs of youth should not be underestimated in developing interventions for career aspirations and choices.
CRIS-Team Scopus Importer:2025-03-21
Keywords: Academic self-concept; Career aspirations; Competence beliefs; STEM; Value beliefs